Perubahan Struktur Anatomi Kayu akibat Pemanasan dengan Microwave Wood Anatomical Changes due to Microwave Heating - Krisdianto Krisdianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
Microwave technology has been developed for wood material in the last few decades. The aim of micro waving wood material is to solve the problem of wood processing, such as drying time and permeability. During microwave radiation, the wood structure has been changed microscopically as well as macroscopically. Microscopic modification includes ruptured of ray cell parenchyma tissue, breakage of pit aspiration and open tylosis blockade in vessels. While, macroscopic modification includes checks radially